Sept grands marchands catholiques français participant au commerce avec la Nouvelle-France (1660-1715) - Bosher, J. (Revue d'histoire de l'Amérique française, 1994)
Keywords: Français; Marchands

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Habitants, autorités et délits en Nouvelle-France: les Montréalais et la traite des fourrures - Robichaud, Léon (Tu sais, mon vieux Jean-Pierre. Essays on the Archeology and History of New France and Canadian Culture in Honour of Jean-Pierre Chrestien, 2017)
Keywords: Délinquance; Fourrure

Montréal, plaque tournante des explorations françaises en Amérique - Conciatori, Christine (Cap-aux-Diamants, 2001)
Keywords: Français

Les Indiens, la fourrure et les Blancs - Trigger, Bruce Graham (Boréal et Seuil, 1992)
Keywords: Autochtones; Fourrure; Français

La ville aux frontières: les perles de traite à Montréal aux XVIIe et XVIIIe siècles - Lamothe, Francis (Université de Montréal, 2006)
Keywords: Archéologie; Autochtones; Français

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale

Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois

Reconstruction des technologies de production métallique employées par les artisans européens et amérindiens du XVIe au XVIIIe siècle au Canada - Treyvaud, Geneviève (Université Laval, 2013)
Keywords: Archéologie; Autochtones; Britanniques; Français

Jardiner en Nouvelle-France - Tairraz, Monique (Continuité, 2003)
Keywords: Jardins

La traite des pelletries aux XVIIe et XVIIIe siècles - Delâge, Denys (Les Cahiers des Dix, 2016)
Keywords: Autochtones; Britanniques; Fourrure; Français; Métis

The Craftsmen of New France - Moogk, Peter N. (Université de Toronto, 1973)
Keywords: Apprentissage; Artisans

S'enraciner en Nouvelle-France - Dickinson, John (Pour le Christ et le Roi. La vie au temps des premiers Montréalais, 1992)

Orfèvres et bijoutiers du Régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1930)
Keywords: Bijouterie; Orfèvres

Le Canal Lachine sous le régime français - Bonin, R. (Bulletin des recherches historiques, 1936)
Keywords: Lachine (canal)

La bourse de Montréal sous le régime français - Massicotte, E.-Z. (Canadian Antiquarian and Numismatic Journal, 1915)

Les arpenteurs de Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1918)
Keywords: Arpenteurs

La boulangerie à Montréal sous le régime français - Montbriand, Monique (Cahier de la Société historique de Montréal, 1985)
Keywords: Boulangerie

L’eau-de-vie en Nouvelle-France, 1629-1672 - Lamontagne, Roland (Université de Montréal, 1951)
Keywords: Alcool

Une chambre de commerce à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Keywords: Marchands

L’industrie du bois en Nouvelle France au 18e siècle - Richard, Claude (Université de Montréal, 1973)
Keywords: Bois de chauffage

Liberté économique et politique des Canadiens sous le Régime français - Bilodeau, Rosario (Université de Montréal, 1956)

Le partage des subsistances au Canada sous le régime français - Dechêne, Louise (Boréal, 1994)
Keywords: Céréales

L'île aux Tourtes (1703-1727) et les perles de traite dans l'archipel montréalais - Murray, Annie-Claude (Université de Montréal, 2008)
Keywords: Autochtones; Communautés religieuses; Fourrure; Français; Missions

La chaloupe à quille en Nouvelle-France: une embarcation et son milieu - Larochelle, Anne-Marie (Université de Montréal, 2008)
Keywords: Archéologie; Construction navale

Les armes à feu portatives en Canada sous le régime français - Bouchard, Russel (Université Laval, 1982)
Keywords: Armes

Power and Subsistence: The Political Economy of Grain in New France - Dechêne, Louise (McGill-Queen's French Atlantic Worlds Series, 2018)
Keywords: Céréales

Les syndics des négociants et la réglementation commerciale en Nouvelle-France, 1717-1760 - Roy, Dave (Université de Sherbrooke, 2013)
Keywords: Marchands; Syndics

Les conditions techniques de l'habitant canadien-français aux XVIIe et XVIIIe siècles - Séguin, Robert-Lionel (Université Laval, 1958)

Bacchus en Canada: boissons, buveurs et ivresses en Nouvelle-France, XVIIe-XVIIIe siècles - Ferland, Catherine (Université Laval, 2004)
Keywords: Alcool; Céréales

Le bétail et l’activité économique en Nouvelle-France: La vente et la location - D’Amour, Valérie (Revue d'histoire de l'Amérique française, 2002)

Le grain, la meule et les vents: le métier de meunier en Nouvelle-France - Laperle, Dominique (GID, 2003)
Keywords: Meunerie

Jardins d'un autre temps. Deux jardins dans l'esprit de la Nouvelle-France - Tairraz, Monique (Maison Saint-Gabriel et Musée du Château Ramezay, 2001)
Keywords: Alimentation; Jardins; Maison Saint-Gabriel; Ramezay (château de)

La ferme Saint-Gabriel des sulpiciens à la Pointe Saint-Charles. Partie I: le Régime français - Douaire, Gilles (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Pointe-Saint-Charles; Saint-Gabriel (ferme); Seigneurie; Sulpiciens

Auberges et Cabarets d'Autrefois. Notes sur l'industrie de l'hôtellerie à Montréal sous le régime français - Massicotte, E.-Z. (Mémoires et comptes rendus de la Société royale du Canada, 1927)
Keywords: Auberges; Cabarets; Hôtellerie

Le nectar et l’ambroisie. La consommation des boissons alcooliques chez l’élite de la Nouvelle-France au XVIIIe siècle - Ferland, Catherine (Revue d'histoire de l'Amérique française, 2005)
Keywords: Alcool; Bourgeoisie

N’être plus la déléguée de personne: une réévaluation du rôle des femmes dans le commerce en Nouvelle-France - Noel, Jan (Revue d'histoire de l'Amérique française, 2009)
Keywords: Femmes; Fourrure; Marchands

Les meuniers dans la région de Montréal à l'époque de la Nouvelle-France (1642-1760): alliances matrimoniales et reproduction sociale - Laperle, Dominique (Université de Montréal, 1996)
Keywords: Famille; Mariage; Meunerie

Ce qui échappe à la Raison d'État: stratégies discursives des intendants de la Nouvelle France confrontés à la contrebande des fourrures, 1715-1750 - Roy, Gilles L. (Université de Montréal, 2018)
Keywords: Autochtones; Criminalité; Fourrure; Marchands

Le risque comme culture de la temporalité - Niget, David; Petitclerc, Martin (Pour une histoire du risque: Québec, France, Belgique, 2012)

The Times and Trials of a Distinctive Colony: 1702-1760 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Alimentation; Artisans; Autochtones; Britanniques; Capitulation; Esclaves; Fortifications; Français; Grande Paix de Montréal; Marchands; Noirs; Seigneurie

On the Ruins of Hochelaga: 1535-1650 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Autochtones; Cartier, Jacques; Chomedey de Maisonneuve, Paul (Maisonneuve, Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance, Jeanne; Société de Notre-Dame de Montréal

Sur les décombres d'Hochelaga, 1535-1650 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Autochtones; Cartier, Jacques; Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance, Jeanne; Société de Notre-Dame de Montréal

Carrières d'engagés du commerce des fourrures canadien au XVIIIe siècle - Wien, Thomas (Marchés, migrations et logiques familiales dans les espaces français, canadien et suisse, 18e-20e siècle, 2005)
Keywords: Engagés; Fourrure